Adjusting to global economic change : the dangerous road ahead - Levine, Robert A.; Rand eBooks (Santa Monica, CA : RAND, 2009)
The author combines macroeconomic history with a brief exposition of economic theory that stems from and explains that history and explores how that experience may apply to the future. He examines the Great Depression, World War II and the following prosperous quarter century, the stagflation and recovery of the 1970s and 1980s, the information technology boom that lasted through the 1990s, and the current economic crisis. In most macroeconomic crises, the worst case-depression or inflation-is fairly clear, and modern policymakers have the tools at hand to cope. He warns that the worst case now may be both-stagflation-and makes some brief suggestions about the new tools needed and policy suggestions for escaping the worst effects of the crisis.
"RAND Pardee Center."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Economic development; Economic forecasting -- United States; Economic policy; Financial crises -- United States; United States -- Economic conditions; Electronic books